ANALISIS POTENSI DAERAH DALAM PENGEMBANGAN KOMODITI UNGGULAN KABUPATEN BOJONEGORO TAHUN 2014-2018 - Cholid Mutawaly Haydar; Wahyu Hidayat; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2019)
The object of this study is an analysis of the potential of the region in developing superior commodities in Bojonegoro Regency data obtained from the Central Statistics Agency for Bojonegoro Regency and East Java Province. This study uses Static Location Quetien (SLQ) analysis, Dynamic Location Quetien (DLQ), Location Quetien (combination of SLQ and DLQ), Classic Shift Share, and Klassen Typology. The base sector in Bojonegoro Regency is. Agriculture, forestry and fisheries sector; mining and excavation sector; information and communication sector; government administration, defense and mandatory social security sectors. From the results of the Classical Shift Share analysis it is known that the results of the growth rate of the mining and quarrying sector in Bojonegoro Regency have the highest value among the other sectors which is 32,678,357. Sectors included in the fast-forward and fast-growing category in Bojonegoro Regency are the wholesale and retail trade sectors; provision of accommodation and food and drink; real estate sector; and the company's service sector.